Examining the trimester-specific effects of low gestational weight gain on birthweight: the BOSHI study. (22nd April 2021) - Oba, Mari S.; Murakami, Yoshitaka; Satoh, Michihiro; Murakami, Takahisa; Ishikuro, Mami; Obara, Taku; Hoshi, Kazuhiko; Imai, Yutaka; Ohkubo, Takayoshi; Metoki, Hiroto
Abstract: Low gestational weight gain (GWG) is a known risk factor of low birthweight. Although studies have previously examined the associations between GWG and birthweight, the period-specific effects of low GWG in each trimester remain unclear. This study aimed to quantify the trimester-specific direct effects of low GWG in Japanese women on birthweight. Using perinatal data from a cohort study, we analyzed pregnant women delivered at an obstetrics/gynecology hospital between October 2006 and May 2010. We focused on women with a pre-pregnancy body mass index (BMI) below 25 kg/m 2 . The exposure was low GWG. The gestation period was subdivided into trimesters, and the direct effects of low trimester-specific GWG on birthweight were estimated using marginal structural models. These models were guided by a direct acyclic graph that incorporated potential confounders, including pre-pregnancy BMI, age, smoking during pregnancy, height, and parity. We analyzed 563 women and their families. The mean cumulative GWG by the end of the first, second, and third trimesters was 0.9, 6.2, and 10.7 kg, respectively. Approximately 14.0% of the women gained total weight below the range recommended by Japanese Ministry of Health, Labour and Welfare. The direct effects of low GWG on birthweight were 65.9 g (95% confidence interval: 11.4, 120.5), −195.4 g (−263.4, −127.4), and −188.8 g (−292.0, −85.5) for the first, second, and third trimesters, respectively. Insufficient weight gain in the second and third trimesters had a negative impact on birthweight after adjusting for pre-pregnancy BMI and other covariates.